Artificial Intelligence and Sexual Offences: An Analysis of Deepfake Pornography in Light of Criminal Law - Januário, Túlio Felippe Xavier (Teisė, 2025)
This paper explores the legal implications of non-consensual sexual deepfakes, specifically analyzing whether the creation, distribution, exhibition, or possession of such content involving adults or minors could be considered sexual offenses under the Portuguese law. By applying a deductive methodology, the study reviews Portuguese, European, North American, and Brazilian legal frameworks, doctrines, and case law related to sexual crimes and Artificial Intelligence (AI), applying them to the issue of deepfakes.The research begins by discussing the increasing prevalence and impact of non-consensual sexual deepfakes, a form of digital manipulation where AI is used to superimpose a person’s face onto someone else’s body in fabricated explicit content. With the rise of easily accessible deepfake technology, the realism of such videos has made it increasingly difficult to distinguish them from authentic material, resulting in significant harm to victims, both adults and minors. This includes emotional and reputational damage, as well as severe psychological consequences such as PTSD, anxiety, and depression, particularly among adults, and developmental harm in the case of minors. The research also highlights the alarming potential for deepfakes to depict child sexual abuse, exacerbating concerns about the exploitation of minors.The study investigates whether non-consensual sexual deepfakes could be classified as criminal offenses under the Portuguese law. It finds that, while the current legal provisions effectively address deepfakes involving minors, a distinction must be made between two types of virtual child pornography: fully virtual representations, and those involving partially real images of minors. Only the latter, where real children’s images are used, should be classified as a crime, as it violates the minor’s development conditions.For deepfakes involving adults, however, the research identifies a legal gap. Existing offenses, such as ‘computer fraud’, ‘illicit recordings or photographs’, or ‘aggravated defamation’, may cover some aspects of deepfake cases, but they do not adequately address the unique harm caused by non-consensual sexual deepfakes. The paper argues that a new criminal offense should be introduced specifically to protect sexual privacy and prevent the creation or distribution of non-consensual sexual deepfakes involving adults. Drawing on the Brazilian legal framework as a model, the study suggests the implementation of tailored provisions that criminalize these acts in order to safeguard the victims’ sexual privacy.The study concludes by emphasizing the need for a legal reform that would balance technological advancements with individual rights. While the paper cautions against excessive expansion of criminal law or a moralistic approach to sexual crimes, it advocates for the creation of specific legal protections against non-consensual sexual deepfakes, while acknowledging the enduring societal impact of this issue. These solutions would help address the harmful effects of deepfakes and provide better legal safeguards for victims of this rapidly evolving digital phenomenon.